The biblical sources of morality - Ghidelli, Carlo (Medicina e Morale, 1988)
In the context of a "Residential Course in Bioethics," this report obviously stands as a contribution at the foundational level. In this respect it relates to other reports, from which, however, it must be clearly and adequately distinguished. In other words, I intend to respect to the utmost the biblical framework that has been indicated to me and that I now point out to you as a fertile and promising field for every man of good will who intends to ethically ground his prass.